Expanding Effective Employment Based on the Development of the Renewable Energy Sector in Uzbekistan - Doctorant (PhD) Elmonov Bekmurod Ermat ugli (Zien Journals, 2022)
The article examines ways to ensure inclusive and sustainable development based on effective employment. The main characteristics of effective employment and the mechanisms of its provision are analyzed. The level of employment, wages, working conditions and its prospects in the field of renewable energy are studied. Prospects of solar and wind power stations in Uzbekistan and employment of the population are analyzed. It was determined that a 1% increase in productivity in agriculture in Uzbekistan changes the structure of employment by a total of 0.32%, and in industry and services it affects the change of employment by 0.14% and 0.04%, respectively
Keywords: demographics; inclusive and sustainable development; climate change; productive employment